ChemInform Abstract: Vasicine Catalyzed Direct C—H Arylation of Unactivated Arenes: Organocatalytic Application of an Abundant Alkaloid. Issue 1 (7th January 2014) - Sharma, Sushila; Kumar, Manoranjan; Kumar, Vishal; Kumar, Neeraj
Abstract The naturally occurring alkaloid vasicine is developed as an efficient catalyst for the formation of biaryls and isomeric terphenyls via transition metal‐free coupling of unactivated arenes with aryl iodides and bromides.